IMPLIKASI ASAS RETROAKTIF TERHADAP KEABSAHAN AKTA NOTARIS/PPAT DALAM PEMBERIAN HAK GUNA BANGUNAN BAGI PERSEROAN TERBATAS - Made Gelgel (University of Udayana, 2017)
Further and deeper research into the validity of the Retroactive Principle is required in order to provide assertiveness about the arrangement of Retroactive Principles in the field of agreement law in the Indonesian legal system, especially the Building Rights Agreement in Agrarian Law and the existence of obscure legal norms in the case of the legal Notary / PPAT to the granting right of building use for a period of validity is reviewed according to the provisions of Article 28 of Regulation of Head of National Land Agency Number 2 Year 2013 concerning the Delegation of Authority of Land Rights and Land Registration Activity and by using case approach of PT. Pan Pacific Nirwana Resort. This research is a normative legal research that is derived from the existence of obscurity of legal principle and legal norm contained in the provisions of Law Number 5 Year 1960 on Basic Agrarian Law Basic (UUPA) in the provisions of Article 30 and Article 28 Regulation of Head of National Land Agency No. 2 of 2013 on the Delegation of Authority of Land Rights and Land Registration Activities. The conclusion of this research in Agrarian Law there is legal uncertainty in the concept of law building rights agreement with a period of time that is still running and the future is approved by a new regulation by the government which caused the previous agreement to occur normatively contradictory whether using retroactive or non-retroactive principle and the validity of deed Notary / PPAT in the granting of right to building to limited liability company which is still valid time is reviewed according to UUPA, Article 28 Regulation of Head of National Land Agency Number 2 Year 2013 regarding Delegation of Authority of Land Rights and Land Registration Activity and Article 1320 Privat Law and by using approach case PT. Pan Pacific Nirwana Resort is not valid. Penelitian lebih lanjut dan mendalam terhadap keberlakuan Asas Retroaktif diperlukan dalam rangka memberikan ketegasan tentang pengaturan Asas Retroaktif [1] di bidang hukum perjanjian dalam sistem hukum Indonesia khususnya perjanjian Hak Guna Bangunan dalam Hukum Agraria serta masih adanya kekaburan norma hukum dalam hal keabsahan akte Notaris/PPAT terhadap Perseroan Terbatas dalam pemberian Hak Guna Bangunan yang jangka waktunya masih berlaku dikaji menurut ketentuan Pasal 28 Peraturan Kepala Badan Pertanahan Nasional Nomor 2 Tahun 2013 tentang Pelimpahan Kewenangan Pemberian Hak Atas Tanah Dan Kegiatan Pendaftaran Tanah serta dengan menggunakan pendekatan kasus PT. Pan Pasific Nirwana Resort. Penelitian ini merupakan penelitian hukum normatif yakni beranjak dari adanya kekaburan asas hukum dan norma hukum yang terdapat di dalam ketentuan Undang-Undang Nomor 5 Tahun 1960 tentang Peraturan Dasar Pokok-pokok Agraria (UUPA) dalam ketentuan Pasal 30 dan Pasal 28 Peraturan Kepala Badan Pertanahan Nasional No. 2 Tahun 2013 tentang Pelimpahan Kewenangan Pemberian Hak Atas Tanah Dan Kegiatan Pendaftaran Tanah. Kesimpulan dari penelitian ini dalam Hukum Agraria terdapat ketidakpastian hukum dalam konsep hukum perjanjian Hak Guna Bangunan dengan jangka waktu yang masih berjalan dan ke depannya di sahkan suatu peraturan baru oleh pemerintah yang menyebabkan perjanjian sebelumnya terjadi pertentangan secara normatif apakah menggunakan asas retroaktif atau non retroaktif dan keabsahan Akta Notaris/PPAT dalam Pemberian Hak Guna Bangunan terhadap Perseroan Terbatas yang jangka waktunya masih berlaku dikaji menurut UUPA, Pasal 28 Peraturan Kepala Badan Pertanahan Nasional Nomor 2 Tahun 2013 tentang Pelimpahan Kewenangan Pemberian Hak Atas Tanah Dan Kegiatan Pendaftaran Tanah jo Pasal 1320 KUH Perdata serta dengan menggunakan pendekatan kasus PT. Pan Pasific Nirwana Resort adalah tidak sah.